2015
DOI: 10.1242/jeb.114223
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of urea transporters in vertebrates: adaptation to urea's multiple roles and metabolic sources

Abstract: In the two decades since the first cloning of the mammalian kidney urea transporter (UT-A), UT genes have been identified in a plethora of organisms, ranging from single-celled bacteria to metazoans. In this review, focusing mainly on vertebrates, we first reiterate the multiple catabolic and anabolic pathways that produce urea, then we reconstruct the phylogenetic history of UTs, and finally we examine the tissue distribution of UTs in selected vertebrate species. Our analysis reveals that from an ancestral U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 101 publications
0
22
0
Order By: Relevance
“…It is possible that differences in arginine content between the yolk and commercial trout pellets and in overall feeding rates, both of which were not measured in the present study, could have contributed to an increased urea load following the onset of exogenous feeding. Recently, it has been suggested that the expression of UTs in nonureagenic tissues may be integral in limiting the internal accumulation of urea, preventing a "back up" of the arginase system via a mass action effect (13). This notion is supported by the observation that when 55 dph trout were loaded with exogenous urea, gill UT gene expression increased (Fig.…”
Section: Perspectives and Significancementioning
confidence: 85%
See 2 more Smart Citations
“…It is possible that differences in arginine content between the yolk and commercial trout pellets and in overall feeding rates, both of which were not measured in the present study, could have contributed to an increased urea load following the onset of exogenous feeding. Recently, it has been suggested that the expression of UTs in nonureagenic tissues may be integral in limiting the internal accumulation of urea, preventing a "back up" of the arginase system via a mass action effect (13). This notion is supported by the observation that when 55 dph trout were loaded with exogenous urea, gill UT gene expression increased (Fig.…”
Section: Perspectives and Significancementioning
confidence: 85%
“…In most fish species, urea transport across epithelia occurs via a facilitated diffusion urea transporter (UT) (15,33,34). There are three UT isoforms in fish: UT-A, UT-C, and UT-D (13). In zebrafish, UT-A is expressed in the gills, while both UT-A and UT-C are expressed in the kidney (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatic OUC is induced in lungfish and in the Singhi catfish Heteropneustes fossilis during terrestrial sojourns, and urea accumulates in the tissues until water returns (Table 4). During reimmersion of lungfish, the facilitated urea transporter is up-regulated to promote rapid elimination of urea (Wood et al, 2005;Hung et al, 2009;LeMoine and Walsh, 2015). In contrast, a few amphibious species simply store glutamine during air exposure (Table 4); this can be easily degraded by glutaminase to glutamate and NH 4 + when water returns.…”
Section: Nitrogen Excretionmentioning
confidence: 99%
“…A recent review analyzed the evolution of urea transporters in vertebrates (36). This analysis showed that three homologues, UT-A, UT-C, and UT-D, evolved from a single ancestral UT in piscine lineages, followed by a reduction to a single UT-A (36).…”
Section: Ut-amentioning
confidence: 99%